Ornithosuchidae: a group of Triassic archosaurs with a unique ankle joint - Von Baczko, Belen (2013)
The ornithosuchids were a group of archosaurs with body lengths ranging from 2 to 4 m recorded from Upper Triassic beds in Argentina and Scotland. The group was defined as a nodebased clade including Ornithosuchus longidens, Riojasuchus tenuisceps, Venaticosuchus rusconii and all descendants of their most recent common ancestor. The ornithosuchids are diagnosed by the following apomorphies observed in the three known species of the clade: downturned premaxilla; premaxilla-maxilla contact with a diastema in the alveolar margin equal in length to two teeth; palatine-pterygoid fenestra; and orbit with a distinct ventral point surrounded by ´V´-shaped dorsal processes of the jugal. The most remarkable postcranial apomorphy of the group is the presence of the so-called crocodile reversed ankle joint, a condition that seems to be unique for the ornithosuchids among amniotans. The systematic history of Ornithosuchidae is complex and Ornithosuchus was allied with dinosaurs or phytosaurs prior to the implementation of numerical hylogenetic analyses. Currently, there is consensus that Ornithosuchidae is positioned within Pseudosuchia, but their phylogenetic position within the group remains strongly debated. Nevertheless, all hypotheses agree in inferring an extremely long ghost lineage at the base of the clade. The presence of derived pseudosuchians in the late Olenekian produces a ghost lineage of c.16-18 millions of years for Ornithosuchidae, indicating that only the late evolutionary history of the clade is currently sampled in the fossil record.